Um artesão de matrioshkas Ficção histórica e metaficção em Rubem Fonseca - Leite, Bruno Ricardo de Souto (2014)
This thesis analyzes the metafictional devices in Rubem Fonseca s short stories and novels, including those which deal with historical events and characters, thus merging fiction and History. To accomplish this, we found support in theoreticians who study metafiction, a tendency which marks Postmodernism in literature, such as Linda Hutcheon (1991), Patricia Waugh (2003) and Gustavo Bernardo (2010). One of the most respected Brazilian fiction writers, Rubem Fonseca debuted in the sixties, tracing his own path within fictional Brazilian prose, not only due to the violent narratives, a feature for which he is best known, but also for the self-reflexive, self-aware and digressive nature of his texts. Accused of being repetitive, it is possible to notice that, though his characters are generally types (the cultivated artist, the detective, the stud ), he usually experiments with form, varying the narrative focus to interweave narrative layers and to parody genres: O Caso Morel, for instance, is an example of a crime novel which implodes the crime novel; the short story H.M.S. Cormorant em Paranaguá, in turn, is a tribute to the brazilian Romantic second generation, represented by Álvares de Azevedo, in a post-modern pastiche conformation. Rubem Fonseca s fifty-year work sheds light over matters which are the order of the day , such as the tripod artist-society-market, and introduces another point of view on the historical past including culture s History, specially literature s. The narratives hereby analyzed test the limits which separate or not fiction from the so called reality, and we classify them into the following categories: novelized autobiography, biographical novel, postmodern historical novel, pastiche, historiographic metafiction and crime metafiction.